Descriptive study family informational support for quality of life of visual impairement children in covid-19 pandemic - Sentya Rizky Susanti; Amin Samiasih; Dera Alfiyanti; Mariyam Mariyam (Universitas Muhammadiyah Semarang, 2022)
Family informational support for visually impaired children in quality of life must be a concern during the Covid-19 pandemic. The research aim is to describe the quality of life in physical, psychological, social, and environmental of visual impairment children, also to provide family informational support in Covid-19 pandemic at SLB Negeri Semarang. The method of research is a descriptive study with univariate analytics. The total sample is 25 respondent visual impairment children at SLB Negeri Semarang with their parents. This research is using total sampling. Results from it are most of the respondents with visual impairments have a good physical quality of life is about 21 respondents (84%), psychological quality of life in a good category is about 13 respondents (52%), quality of social life in a good category is about 16 respondent (64%), and environmental quality of life in a bad category is about 13 people (52%). Most respondents as a parent of blind children have a good category in family informational support is about 15 respondents (60%). The conclusion is most of the respondents with visual impairment respondent have a good category for quality of life of physical, psychological, social, and bad category for quality of life environmental. Family informational support with parents respondents mostly has a good category. The recommendation is this research can give concern to parents for always giving a family informational support to increase the quality of life of visually impaired children.